2014
DOI: 10.4018/ijssoe.2014070102
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Technology Acceptance in Intensive Care Units

Abstract: The process of deploy a technology in critical services need to be very careful planned and processed. As an example it is the Intensive Care Unit (ICU). In the ICU the patients are in critically ill conditions and there are not available time to make experiences or to develop incomplete systems. With the objective to improve the implementation process, the same should be accompanied in order to understand the environment and user behaviour. In this case and with the goal to evaluate the implementation process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Some of the most relevant works in the health care field are presented next. An assessment of the INTCare system, used in the ICU of CHP, was performed using the constructs proposed by TAM and a questionnaire-based approach guided by the Delphi methodology [10]. Through the best (PEOU) and worst (UB) acceptance results, the study showed that health professionals were satisfied with the technology implemented in terms of innovation and functionality but complained about the real-time performance and responsiveness of equipment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most relevant works in the health care field are presented next. An assessment of the INTCare system, used in the ICU of CHP, was performed using the constructs proposed by TAM and a questionnaire-based approach guided by the Delphi methodology [10]. Through the best (PEOU) and worst (UB) acceptance results, the study showed that health professionals were satisfied with the technology implemented in terms of innovation and functionality but complained about the real-time performance and responsiveness of equipment.…”
Section: Related Workmentioning
confidence: 99%
“…This scale allows the participant to specify their level of agreement with a certain statement [12]. The use of a short 5-point scale, with two negative values (1, 2), two positive values (4, 5) and a neutral value (3), narrows the results, avoiding their dispersion and reducing inaccuracy [10].…”
Section: Additional Commentsmentioning
confidence: 99%
“…In order to understand the level of acceptance of health professionals regarding the use of the tool presented in this dissertation, a questionnaire was developed and interviews were conducted, following the methodology and con-structs of TAM, a model that evaluates a number of factors that influence their decision to use, how to use and when to use this technology [15].…”
Section: Table 1 Swot Analysismentioning
confidence: 99%
“…This study contributes to understanding how many values are noise and what set of values can be considered a critical event (Portela, Gago, et al, 2012;Portela, Gago, et al, 2013). The use of critical incidents, based on data, improves the sensitivity of the data mining models (Portela, Pinto, & Santos, 2012;Portela, Oliveira, Santos, Abelha, Machado, Silva & Rua, 2014;Braga, Portela, & Santos, 2014; while the system provides a continuous assessment process (Aguiar et al, 2013;Portela, Aguiar, Santos, Silva, & Rua, 2013;Portela, Aguiar, et al, 2014;.…”
Section: Intcare Systemmentioning
confidence: 99%